The competitive role of C–H⋯X (X = F, O) and π–π interactions in contributing to the degree of charge transfer in organic cocrystals: a case study of heteroatom-free donors with p-fluoranil (FA). Issue 36 (1st September 2022) - Gao, Jiaoyang; Guo, Jinjia; Chen, Yi; Deng, Shunlan; Lu, Qidong; Ren, Yuxin; Wang, Xiaoming; Fan, Haibo; Teng, Feng; He, Xuexia; Jiang, Hui; Hu, Peng
Abstract : Four binary organic charge transfer cocrystals were grown by the slow cooling method. The competitive role of C–H⋯X (X = F, O) and π–π interactions in contributing to the degree of charge transfer in the cocrystals was investigated. Abstract : Weak intermolecular interactions, such as π–π interactions, hydrogen bonds, halogen bonds and charge transfer interactions, are important for tuning the physical properties of organic charge transfer cocrystals. However, it is still a controversial question which kind of weak intermolecular interaction dominates the degree of charge transfer. In this work, four four-ring-fused donors (triphenylene: TP; benz[ a ]anthracene: BAA; pyrene and chrysene) without heteroatoms were selected to grow charge transfer cocrystals with p -fluoranil (FA) through slow cooling using chlorobenzene and benzene as solvents, which may exclude the effect of heteroatoms in donor molecules. Pyrene–FA and TP–FA exhibit a black rod-like morphology and a red rod-like morphology, respectively, while both BAA–FA and chrysene–FA exhibit black plate shapes. The impact of weak intermolecular interactions (C–H⋯X (X = F, O) interactions, π–π interactions and charge transfer interactions) on the degree of charge transfer (DCT) was investigated. The DCT is affected by the interplanar distance of the donor–acceptor (D–A) along the π–π direction, which is increased with the decrease of the D–A interplanar distance. The results indicate that the cocrystal with stronger charge transfer and π–π interactions could lead to a larger DCT. Although stronger C–H⋯F (2.4833(2) Å) and C–H⋯O interactions (2.5137(5) Å) were observed in BAA–FA and TP–FA, respectively, the DCT was still dominated by charge transfer and π–π interactions. The results suggest that it is crucial to consider the selection of the donors when discussing the contribution of different intermolecular interactions toward the DCT.